Social Interactions and Labor Market Outcomes in Cities - Yves Zenou (Research Institute of Industrial Economics (IFN), 2008)
We develop a model where information about jobs is essentially obtained through friends and relatives, i.e. strong and weak ties. Workers commute to a business center to work and to interact with other people. We find that housing prices increase with the level of social interactions in the city because information about jobs is transmitted more rapidly and, as a result, individuals are more likely to be employed and to be able to pay higher land rents. We also show that, under some conditions, workers using more their weak ties than strong ties to find a job receive a higher wage. We finally demonstrate that workers living far away from jobs pay lower housing prices but experience higher unemployment rates than those living close to jobs because they mainly rely on their strong ties to obtain information about jobs.
Keywords: A14; J60; R14; 330; Weak Ties; Labor Market; Social Networks; Land Rent; Soziale Beziehungen; Immobilienpreis; Informationsversorgung; Friktionelle Arbeitslosigkeit; Weiße; Schwarze; Städtischer Arbeitsmarkt; Dynamisches Modell; Theorie